Impact of Macroeconomic Dynamics on Maritime Transport Development: A Quantitative Analysis - Samekto, Agus Aji (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This study investigates the dynamic interactions between macroeconomic variables and maritime transport development using time series data from 2000 to 2024. A vector autoregressive (VAR) model was employed to examine the causal linkages among gross domestic product (GDP) growth, fuel price volatility, industrial production, and the maritime freight index. Drawing upon recent literature, the results reveal a statistically significant bidirectional causality between GDP growth and maritime transport performance, confirming the sector’s cyclical dependence on broader economic fluctuations. The findings also show that fuel price volatility exerts a negative long-term effect on freight index growth, while industrial production acts as a mediating factor enhancing maritime capacity utilization. Further quantitative analysis indicates that a one-percent increase in GDP leads to an average 0.47 percent growth in maritime freight index performance, whereas a one-percent rise in fuel price volatility reduces it by 0.21 percent. The analysis supports the assertion that maritime logistics efficiency is closely linked to macroeconomic stability, technological adaptation, and energy transition strategies. The study highlights the need for integrated policy frameworks that synchronize macroeconomic stabilization with maritime infrastructure investments, digitalization, and decarbonization strategies to ensure sustainable maritime growth. This paper contributes to contemporary discourse by offering empirical evidence of the macroeconomic sensitivity of maritime transport development in emerging economies, emphasizing quantitative linkages often underexplored in existing literature.